Characterisation of highly irradiated 3D trench silicon pixel sensors for 4D tracking with 10 ps timing accuracy - Borgato, F.; Cardini, A.; Cossu, G. M.; Dalla Betta, G. F.; Garau, M.; La Delfa, L.; Lai, A.; Lampis, A.; Loi, A.; Obertino, M. M.; Simi, G.; Vecchi, S. (Frontiers in Physics, 2024)
3D trench silicon pixel sensors, recently developed by the TimeSPOT collaboration, have shown excellent performance in terms of spatial resolution, timing precision and detection efficiency. The combination of these three features make them one of the best candidate for inner tracking detectors operating in high luminosity hadron colliders experiments. This article presents systematic characterisations of these devices made with minimum ionising particles on irradiated sensors with neutrons up to 2.5 • 10 16 1 MeV n eq cm -2 .The results show that 3D trench pixels have extremely high resistance to radiation. The measured time resolution and the detection efficiency of irradiated sensors match those of non-irradiated ones if a slightly higher bias voltage, few tens of Volts, is applied to the pixels. As of today, 3D trench pixels are the only sensors capable of achieving 10 ps time resolution after being irradiated at extremely high fluences, extending by far the capabilities of future tracking systems of HEP experiments operating under extreme conditions.